First images of thunder: Acoustic imaging of triggered lightning. Issue 14 (16th July 2015) - Dayeh, M. A.; Evans, N. D.; Fuselier, S. A.; Trevino, J.; Ramaekers, J.; Dwyer, J. R.; Lucia, R.; Rassoul, H. K.; Kotovsky, D. A.; Jordan, D. M.; Uman, M. A.
Abstract An acoustic camera comprising a linear microphone array is used to image the thunder signature of triggered lightning. Measurements were taken at the International Center for Lightning Research and Testing in Camp Blanding, FL, during the summer of 2014. The array was positioned in an end‐fire orientation thus enabling the peak acoustic reception pattern to be steered vertically with a frequency‐dependent spatial resolution. On 14 July 2014, a lightning event with nine return strokes was successfully triggered. We present the first acoustic images of individual return strokes at high frequencies (>1 kHz) and compare the acoustically inferred profile with optical images. We find (i) a strong correlation between the return stroke peak current and the radiated acoustic pressure and (ii) an acoustic signature from an M component current pulse with an unusual fast rise time. These results show that acoustic imaging enables clear identification and quantification of thunder sources as a function of lightning channel altitude.